Genomic epidemiology of NDM-1-Encoding Plasmids in latin american clinical isolates reveals insights into the evolution of multidrug resistance (2017)
Bacteria that produce the broad-spectrum Carbapenem antibiotic New Delhi Metallo-β-lactamase (NDM) place a burden on health care systems worldwide, due to the limited treatment options for infections caused by them and the rapid global spread of this antibiotic resistance mechanism. Although it is believed that the associated resistance gene blaNDM-1 originated in Acinetobacter spp., the role of Enterobacteriaceae in its dissemination remains unclear. In this study, we used whole genome sequencing to investigate the dissemination dynamics of blaNDM-1-positive plasmids in a set of 21 clinical NDM-1-positive isolates from Colombia and Mexico (Providencia rettgeri, Klebsiella pneumoniae, and Acinetobacter baumannii) as well as six representative NDM-1-positive Escherichia coli transconjugants. Additionally, the plasmids from three representative P. rettgeri isolates were sequenced by PacBio sequencing and finished. Our results demonstrate the presence of previously reported plasmids from K. pneumoniae and A. baumannii in different genetic backgrounds and geographically distant locations in Colombia. Three new previously unclassified plasmids were also identified in P. rettgeri from Colombia and Mexico, plus an interesting genetic link between NDM-1-positive P. rettgeri from distant geographic locations (Canada, Mexico, Colombia, and Israel) without any reported epidemiological links was discovered. Finally, we detected a relationship between plasmids present in P. rettgeri and plasmids from A. baumannii and K. pneumoniae. Overall, our findings suggest a Russian doll model for the dissemination of blaNDM-1 in Latin America, with P. rettgeri playing a central role in this process, and reveal new insights into the evolution and dissemination of plasmids carrying such antibiotic resistance genes.